Cyclitol based metal complexing agents. preference for the extraction of lithium by myo-inositol based crown-4-ethers depends on the relative orientation of crown ether oxygen atoms - Dixit, Shailesh S.; Shashidhar, M. S.; Devaraj, Subramanian (Tetrahedron, 2006)
myo-Inositol derived crown-4-ethers in which two of the oxygen atoms in the crown ether moiety have different relative orientations were prepared. Metal picrate binding studies revealed that the crown ether having 1,3-diaxial orientation shows the highest selectivity for binding to lithium although the crown ether having 1,2-diequatorial orientation exhibited the highest binding constant for lithium picrate. These results suggest that relative binding affinity of metal ions to crown ethers can be tuned by varying the relative orientation of crown ether oxygen atoms. The relevance of these results to the previously observed regioselectivity during the O-substitution of myo-inositol orthoesters is discussed. (c) 2606 Elsevier Ltd. All rights reserved.
Keywords: crown ether; Cyclitol; Inositol; ligand; lithium; metal complex